The Inverse Domino Effect: Are Economic Reforms Contagious? - Gassebner, M.; Gaston, Noel; Lamla, M. (Wiley-Blackwell Publishing, Inc., 2011)
This article examines whether a country's economic reforms are affected by reforms adopted by other countries. Our theoretical model predicts that reforms are more likely when factors of production are internationally mobile and reforms are pursued in other economies. Using the change in the Index of Economic Freedom as the measure of market-liberalizing reforms and panel data (144 countries, 1995–2006), we test our model. We find evidence of the spillover of reforms. Moreover, consistent with our model, international trade is not a vehicle for the diffusion of economic reforms; rather the most important mechanism is geographical or cultural proximity.